2021
DOI: 10.1212/nxi.0000000000001030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Natalizumab Therapy on Intrathecal Immunoglobulin G Production Indicate Targeting of Plasmablasts

Abstract: ObjectivesTo evaluate the long-term effects of natalizumab (NTZ) on different features of intrathecal immunoglobulin (Ig) synthesis in patients with multiple sclerosis (MS) and to quantify the expression of α4-integrin in stages of B-cell maturation.MethodsWe combined a cross-sectional (49 NTZ-treated MS patients, mean treatment duration 5.1 years, and 47 untreated MS patients) and a longitudinal study (33 patients with MS before and during NTZ, mean treatment duration: 4.8 years), analyzing paired serum and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 37 publications
4
16
1
Order By: Relevance
“…Although the number of OCBs reduced after NTZ treatment, OCBs disappeared completely only in 9 patients (9.7%) and OCBs positivity dropped from 94.6% to 86.0%. This was consistent with previous studies reporting a decrease in OCB positivity from a 100% positivity at the baseline to an 84% positivity at the follow-up (n = 73) [14], from an 86% positivity at the baseline to a 76% positivity at the follow-up (n = 33 before and 49 after NTZ treatment) [13] and a 93.3% positivity at the baseline to an 80% positivity at the follow-up (n = 15) [15]. Only one study by Mancuso et al observed a complete disappearance of OCBs in the majority of patients on NTZ with a decrease in the OCB positivity from 92% at the baseline to 42% at the follow-up (n = 24) [17].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Although the number of OCBs reduced after NTZ treatment, OCBs disappeared completely only in 9 patients (9.7%) and OCBs positivity dropped from 94.6% to 86.0%. This was consistent with previous studies reporting a decrease in OCB positivity from a 100% positivity at the baseline to an 84% positivity at the follow-up (n = 73) [14], from an 86% positivity at the baseline to a 76% positivity at the follow-up (n = 33 before and 49 after NTZ treatment) [13] and a 93.3% positivity at the baseline to an 80% positivity at the follow-up (n = 15) [15]. Only one study by Mancuso et al observed a complete disappearance of OCBs in the majority of patients on NTZ with a decrease in the OCB positivity from 92% at the baseline to 42% at the follow-up (n = 24) [17].…”
Section: Discussionsupporting
confidence: 93%
“…This was consistent with recent research showing a negative correlation between a younger age and higher CSF leukocytes [30] but also with a number of studies documenting a higher inflammatory activity in young patients and in early disease stages [25,31,32]. Reductions in the IgG and IgM indices and quotients following NTZ have also been reported previously [13,15,16]. However, only the study by Schluter et al found that NTZ induced a reduction of the IgG index but not the IgM indices in RRMS patients [13].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…From the clinical point of view, emerging evidence shows that disease-modifying treatments (DMTs) may alter intrathecal immunoglobulins production and that intrathecal immunoglobulins may modulate DMT response. For example, natalizumab decreased serum IgM and IgG levels but, in CSF, only IgG indices [ 49 ]. Furthermore, it has been demonstrated that autologous hematopoietic stem cell transplantation (aHSCT) lowered intrathecal immunoglobulin indices and suppressed both IgG and IgM oligoclonal bands, thus challenging the notion that OCBs are unaffected by therapeutic intervention in MS [ 50 ].…”
Section: Discussionmentioning
confidence: 99%